IUFRO in the tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The International Union of Forest Research Organizations (IUFRO) is one of the world's oldest scientific organizations. Its goal is to help coordinate forest research through a permanent programme of close international cooperation between...